An investigation into differentiation in a rural Aotearoa New Zealand secondary science setting He waka eke noa : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University, Manawatū, Aotearoa New Zealand - Vander Zwaag, Carrie Eileen (Massey University, 2018)
Disparity in education is a problem confronting educational researchers and practitioners. Within Aotearoa New Zealand, science education inequity is evidenced in a gap - one of the widest internationally - between high and low performers on international assessments. Māori and students of other non-dominant cultural backgrounds are disproportionally represented at the bottom end of this performance scale. Literature indicates that differentiation – the modification of curriculum and instruction to support students with academically diverse learning needs through adaptations to content, process, or product – is an inclusive teaching and learning strategy with the potential to increase educators’ abilities to meet diverse students’ needs. However, little research or evidence exists to provide teachers with the framework to differentiate effectively in mainstream science classrooms. This mixed methods action research (MMAR) investigation enabled a rural, bicultural Aotearoa New Zealand school community’s years 9 and 10 students (ages 12-15), their science teachers and whānau (families) to firstly, share their perspectives on current classroom practice, and from these perspectives, collaboratively develop, implement and evaluate a differentiated science unit. The study utilised both quantitative and qualitative data collection strategies, including surveys, individual interviews, classroom observations, focus groups, and collaborative professional development and planning sessions. The objective was to expand the evidence base of effective teaching and learning strategies for all learners within diverse mainstream secondary science classrooms including those identified as at risk for under-achievement such as students with learning difficulties, exceptional science talent and of Māori or other non-dominant cultural backgrounds. Findings suggest there is value in teachers using differentiated materials designed for gifted learners when the gifted differentiation principles and practices are adapted and implemented in response to community input. Findings indicate that student engagement and learning in science – for Māori and non-Māori students from across the learning spectrum – improved in all aspects that teachers chose to differentiate, including: relevance of content, assessment and accommodation of student readiness, and variety and choice in process and product. From the research findings, a model of community-driven differentiation, he waka eke noa: differentiation in 3-D (teacher/student/whānau), has been conceptualised that could potentially be a strategy for increasing the quality of culturally responsive science teaching and learning that meets diverse students’ needs both within Aotearoa New Zealand and internationally.
Keywords: Science -- Study and teaching (Secondary) -- New Zealand; Children, Maori -- Education (Secondary) -- New Zealand; Gifted children -- Education (Secondary) -- New Zealand; Rural schools -- New Zealand -- Case studies; Inclusive education -- New Zealand -- Case studies; Individualized instruction -- New Zealand -- Case studies; Mixed ability grouping in education -- New Zealand -- Case studies; Pūtaiao; Mātauranga; Waihanga; Ako; Pūkengatanga